Emancipação e esclarecimento em Habermas - Silva, Ednaldo Firmino da (2014)
This study aims to develop one of the main innovations elucidated by Habermas's theory of communicative action, the debate of enlightenment, emancipation and discourse ethics. The prospect of emancipation gains notoriety in the Enlightenment movement that sought to engender in individuals with an intellectual freedom, political, religious and others. Critics of the Frankfurt School, Adorno and Horkheimer believe that the project of enlightenment left a deep void in meets your ideals, therefore, they believed that the reason was converted into a ratio that deviated alienated the emancipatory project. In Habermas' Philosophical Discourse of Modernity (1985) ranks critically Adorno and Horkheimer, Adorno and Horkheimer emphasizing that might is clutched in myth, as it existed in modernity pretty significant changes. When dealing with the work category, Habermas seek to replace it with language, as it believes that before work presupposes the language. What Habermas is seeking not a deconstruction of Marx's theory, but a reconstruction, in which there is a predominance of language on the job. Thus, the communicative community which individuals make use of language as a means of mutual understanding may attain emancipation. Considering this model, Habermas on discourse ethics has as a moral foundation that is focused on consensus, since the consensus consists in argumentative community. But what happens to the constitution of this community there must be a radical universal validity.